PD-1 blockade therapy in renal cell carcinoma: Current studies and future promises. Issue 2 (February 2015) - Massari, F.; Santoni, M.; Ciccarese, C.; Santini, D.; Alfieri, S.; Martignoni, G.; Brunelli, M.; Piva, F.; Berardi, R.; Montironi, R.; Porta, C.; Cascinu, S.; et al.
Highlights Evasion of immune surveillance, a process defined immune-editing, leads to RCC malignant progression. The PD-1/PD-L1 axis inhibition by targeted-antibodies, increases T-cell proliferation and anti-tumor activity. PD-1 and PD-L1 inhibitors have been tested in RCC, alone or combined with anti-VEGF/VEGFR drugs or other immunotherapies. We discuss the role of PD-1/PD-L1 in RCC, focusing on current clinical studies and future perspectives.